Innovations and Challenges to Reform in Public Service in Realizing Good Governance - Cikusin, Yaqub; Anadi, Yandri Radhi (International Journal of Business, Law, and Education, 2024)
Innovation in public administration reform plays a crucial role in realizing good governance. However, the main issue is resistance to change, which often stems from government employees who are comfortable with the old ways of working and are reluctant to adapt to new methodologies and resource limitations, both in terms of finances and human resources, which often become obstacles in the implementation of effective innovation. This study aims to find out Public Service Innovation in Realizing Challenges to Reform Good Governance in the future. This research is a type of policy research that is analyzed descriptively and qualitatively. The results of the study show that innovation in public services can be carried out with the achievement of changes in mindset and bureaucratic work culture, policy deregulation, organizational simplification, management improvements, arrangement of human resources of the apparatus, strengthening accountability and budget efficiency, strengthening supervision, and improving the quality of public services